Cumulative long-term incidence of postoperative periprosthetic femoral fractures using an uncemented tapered titanium hip stem: 26- to 32-year results - Peitgen, David S.; Innmann, Moritz Maximilian; Merle, Christian; Moradi, Babak; Streit, Marcus R. (The journal of arthroplasty, 2019)
Background - Although falling is becoming a major problem in the elderly, little is known about the long-term incidence of postoperative periprosthetic femoral fractures (PFF) after total hip arthroplasty (THA) using uncemented stems with a minimum follow-up of 26 years postoperatively. - Methods - In a consecutive series, the cumulative incidence of PFF after uncemented THA using a straight, collarless, tapered titanium stem was retrospectively reviewed in 354 hips (326 patients). After a mean follow-up of 28 (26-32) years postoperatively, 179 hips had died and 5 hips had been lost to follow-up. Kaplan-Meier survival analysis was used to estimate cumulative percentage probability of PFF. - Results - At final follow-up, a total of 27 fractures in 27 patients had occurred. In 15 hips, the stem had to be revised, and in 10 the fracture was treated by open reduction and internal fixation. Two patients declined further surgery. The cumulative percentage probability of PFF was 1.6% (95% confidence interval, 0.7 to 3.8) at 10 years and 13.2% (95% confidence interval, 8.5 to 20.2) at 29 years after primary THA. There was no association between the occurrence of fracture and gender, age at primary THA, cup revision, or canal fill index. - Conclusion - Our findings indicate that PFF is the major mode of failure in the long term after uncemented THA using a tapered titanium stem. More research is needed to evaluate the reasons and risk factors for PFF after THA, thus providing better prophylaxis for those at risk and to compare the long-term incidence using different fixation methods and implants. - Level of evidence - IV.